Artificial intelligence for knowledge management : third IFIP WG 12.6 International Workshop, AI4KM 2015, held at IJCAI 2015, Buenos Aires, Argentina, July 25-31, 2015, Revised selected papers /: third IFIP WG 12.6 International Workshop, AI4KM 2015, held at IJCAI 2015, Buenos Aires, Argentina, July 25-31, 2015, Revised selected papers. (2016) - Unknown
No abstract available